Grump : the (fairly) true tale of Snow White and the seven dwarves - Shurtliff, Liesl (Alfred A. Knopf, 2018)
"Ever since he was a dwarfling, Borlen (nicknamed Grump) has dreamed of visiting The Surface, so when opportunity knocks, he leaves his cavern home behind. At first, life aboveground is a dream come true. Queen Elfrieda Veronika Ingrid Lenore (E.V.I.L.) is the best friend Grump always wanted, feeding him all the rubies he can eat and allowing him to rule at her side. But as time goes on, Grump starts to suspect that Queen E.V.I.L. may not be as nice as she seems. When the queen commands him to assist in a fiendish plot against her stepdaughter, Snow White, Grump is in over his head. He's bound by magic to help the queen, but also to protect Snow White. As if that wasn't stressful enough, the queen keeps bugging him for updates through her magic mirror! He'll have to dig deep to find a way out of this pickle - and that's enough to make any dwarf Grumpy indeed."--Jacket.